Traditional Chinese medicine on treating active rheumatoid arthritis: A protocol for systematic review and meta-analysis - Zhang, Lingyue (Medicine (Baltimore), 2020)
BACKGROUND: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease associated with progressive joint damage and disability. There is a lack of effective methods in the treatment of RA currently. Many clinical trials have proved that traditional Chinese medicine (TCM) has obvious advantages in the treatment of RA. In this systematic review, we intend to evaluate the efficacy and safety of TCM for active RA. METHODS: We will search PubMed, the Cochrane Library, Embase, Web of Science, the Chinese National Knowledge Infrastructure Database, Wanfang Data, and Chinese Science and Technology Periodical Database. Simultaneously we will retrieval relevant meeting minutes, eligible research reference lists, symposium abstracts, and grey literatures. Included criteria are randomized controlled trials (RCTs) about TCM for active RA to assess its efficacy and safety. We will use the Revman 5.3 and Stata 13.0 software for data synthesis, sensitivity analysis, meta regression, subgroup analysis, and risk of bias assessment. The Grading of Recommendations Assessment, Development, and Evaluation standard will be used to evaluate the quality of evidence. RESULTS: This systematic review will provide a synthesis of TCM for patients with active RA from various evaluation aspects including tender joint count, swollen joint count, RF, CRP, ESR, DAS28, TCM syndrome evaluation criteria, and adverse events. CONCLUSION: The systematic review will provide evidence to assess the efficacy and safety of TCM in the treatment of patients with active RA. PROSPERO REGISTRATION NUMBER: PROSPERO CRD42019146726